Mind the gap! A survey of the challenges of biomarker commercialization. Issue 1 (January 2020) - Raths, Susan; Parkel, Sven; Bredmose, Jesper; Daussin, Valérie
Highlights: Currently no proven successful commercialization pathway for biomarkers exists. Researchers often value scientific publications over commercialization. TTOs, investors and companies expect a stronger market perspective of researchers. Prices and investments are the biggest hurdles to clinical routine adoption. Clear guidelines for the development of biomarker tests would be an important step. Abstract : 'Mind the gap!' refers to both the gap between the identification and validation of biomarkers and the gap in knowledge between the stakeholder groups, where the researchers who discover the biomarkers often have little knowledge about the commercialization process. This gap is addressed here in a survey with relevant stakeholders conducted by the project 'Biomarker Commercialization' (BIC).